The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.18433/j3g30b
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Small Molecules Immunosuppressants on P-Glycoprotein Activity and T-cell Function

Abstract: -Purpose. P-glycoprotein (Pgp) is a member of the ABC-transporter family that transports substances across cellular membranes acting as an efflux pump extruding drugs out of the cells. Pgp plays a key role on the pharmacokinetics of several drugs. Herein, we have studied the effects of immunosuppressants on Pgp function, assessing rhodamine-123 (Rho123) uptake and efflux in different Tcell subsets. Methods. Different immunosuppressants such as Cyclosporine (CsA), Rapamycin (Rapa) and Tacrolimus (Tac) were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Since CsA induces greater hypertension than tacrolimus (36), besides via inhibition of calcineurin, CsA may cause hypertension also via another mechanism. Indeed, CsA, but not tacrolimus, also inhibits the ABCA1 transporter (25), which is responsible for Cho transport out of the cells (46). Our recent study (45) suggested that CsA causes hypertension by also stimulating the epithelial Na ϩ channel in distal nephron cells via ABCA1-dependent elevation of cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…Since CsA induces greater hypertension than tacrolimus (36), besides via inhibition of calcineurin, CsA may cause hypertension also via another mechanism. Indeed, CsA, but not tacrolimus, also inhibits the ABCA1 transporter (25), which is responsible for Cho transport out of the cells (46). Our recent study (45) suggested that CsA causes hypertension by also stimulating the epithelial Na ϩ channel in distal nephron cells via ABCA1-dependent elevation of cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…[49] In this context, patients (high pumpers) treated with low doses of CsA would show lower drug exposure and this could affect MPA AUC exposure. [17,49] …”
Section: Discussionmentioning
confidence: 99%
“…These immunosuppressants act as substrates and/or inhibitors of Pgp, alter the bioavailability of many concomitantly used drugs, and are potential inducers of drug–drug interactions. [17] …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the difference in P-gp functional activity between GCs-responsive and GCs-nonresponsive patients with ITP was significant only in CD8 + T cells. Llaudó et al [37] also indicated that P-gp inhibitors diminished P-gp activity and T-cell function, especially on CD8 + T cells subsets. These results suggested that CD8 + T cells might contain the main target sites of P-gp in ITP.…”
Section: Discussionmentioning
confidence: 98%